Porous WS2 and W2N powders by hard templating with colloidal silica. Issue 1 (January 2017) - Gibot, P.; Parmentier, J.; Vidal, L.; Schnell, F.; Nouali, H.; Spitzer, D.
Abstract: Meso- and macroporous tungsten disulfide (WS2 ) and tungsten nitride (W2 N) powders were successfully synthesized by reduction of [WO3 /colloidal silica] composites under hydrogen sulfide and ammonia gases respectively. The colloidal silica, marketed as Ludox ®, was used as a hard template and its removal from the composite led to a porosity release. The products were characterized by X-ray diffraction, nitrogen adsorption, mercury porosimetry and electron microscopy. Well-crystallized samples with specific surfaces areas close to ~40 m 2  g −1 were thus synthesized. The present approach might be easily extended to the synthesis of other nitrides and sulfides materials.